Comparison of pleural N‐terminal pro‐B‐type natriuretic peptide, midregion pro‐atrial natriuretic peptide and mid‐region pro‐adrenomedullin for the diagnosis of pleural effusions associated with cardiac failure. Issue 3 (21st March 2013) - Porcel, José M.; Bielsa, Silvia; Morales‐Rull, José L.; Civit, Carme; Cao, Gonzalo; Light, Richard W.; Esquerda, Aureli
<x xml:space="preserve">Abstract</x> NT‐proBNP is a well‐recognized biomarker of pleural effusions associated with cardiac failure. We demonstrate that pleural fluid MR‐proANP has similar discriminating capabilities as NT‐proBNP, whereas the measurement of MR‐proADM is of limited value in this context.